Investigation of the water-stimulated Mg2+ insertion mechanism in an electrodeposited MnO2 cathode using X-ray photoelectron spectroscopy. Issue 4 (9th January 2018) - Sahadeo, Emily; Song, Jaehee; Gaskell, Karen; Kim, Nam; Rubloff, Gary; Lee, Sang Bok
Abstract : In water-containing organic electrolyte, the charge storage of amorphous MnO2 combines Mg(OH)2 formation at the cathode surface and Mg insertion. Abstract : Batteries based on magnesium chemistry are being widely investigated as an alternative energy storage system to replace lithium-ion batteries. Mg batteries have multiple challenges, especially on the cathode side. The divalent Mg ion has slow insertion kinetics in many metal oxide cathodes conventionally used in Li-ion batteries. One solution that has been explored is adding water molecules into an organic electrolyte, which has been shown to aid in Mg insertion and improve performance of manganese oxide (MnO2 ) cathodes. While there have been studies on Mg insertion mechanisms into MnO2 in solely aqueous or organic electrolytes for some crystalline MnO2 polymorphs, our work is focused on water-containing organic electrolyte, where an H2 O to Mg ratio of 6 : 1 is present. In this study, we report results based on ex situ XPS experiments, including both angle resolved and depth profiling studies to assess the surface reactions and determine the mechanism of Mg insertion into an amorphous, electrodeposited MnO2 cathode. We propose that in this mixed electrolyte system, there is a combined insertion/conversion reaction mechanism whereby Mg and H2 O molecules co-insert into the MnO2 structure and a reaction between H2 O and Mg creates an observable Mg(OH)2 layer at the surface of the MnO2 . A more full understanding of the role of the water molecules is important to aid in the future design of cathode materials, especially when determining potential ways to integrate metal oxides in Mg batteries.